Modified starch cement-based material mixing state regulating agent as well as preparation method and application thereof
By modifying the mixing state regulator of starch cement-based materials, the problem of difficulty in maintaining dispersion uniformity of cement-based materials during the mixing, injection molding and curing stages is solved, and the structural uniformity and performance improvement of cement-based materials is achieved.
Patent Information
- Application Number
- CN202411554403.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation of existing cement-based materials, it is difficult to maintain uniform dispersion of system components, and there are phenomena such as water excretion, sedimentation, sand and gravel settlement and stratification, resulting in uneven distribution of structural composition, insufficient strength to meet expectations, and easy to produce cracks and seepage. leak.
Modified starch is used as the mixing state regulator of cement-based materials, and sodium starch octenyl succinate is combined with acrylic monomer through the preparation method to form a cement slurry with good fluidity and dispersion uniformity, and adjust the cement slurry The viscosity and fluidity of the body ensure uniform dispersion and suspension of sand and gravel in the cement slurry.
The structural uniformity and performance of cement-based materials are significantly improved, the settlement, layering and separation of sand and gravel are avoided, and the stability, mechanical properties and durability of cement-based materials are enhanced.
Smart Images

Figure BDA0005116018980000081
Abstract
Description
Technical Field
[0001] The invention relates to a cement-based material admixture, in particular to a modified starch cement-based material mixing state regulator, a preparation method and an application thereof. Background Art
[0002] Cement-based materials mainly refer to cement concrete, which is composed of cement, sand, gravel, water and admixtures. Cement and water form cement paste, which bonds sand and gravel together and forms a whole through the curing process, thus having volume stability, good strength and durability. The preparation process of cement-based materials includes mixing, injection molding and curing processes. The mixing process is to allow cement and water to form cement paste, which will encapsulate fine sand and gravel. The strength and performance of cement-based materials are mainly determined by the performance of cement and the distribution of sand and gravel in cement paste. The ideal structure is that gravel and fine sand are evenly dispersed in cement paste, fine sand is evenly filled and dispersed in the gaps between gravel, and cement paste is evenly distributed around fine sand and gravel to form a continuous structure. This structure of cement-based materials is the basis of its performance and strength.
[0003] In order to make the structure of cement-based materials uniform, it is necessary to maintain the uniform dispersion and distribution of sand, gravel and cement paste in the mixing stage, pouring and molding stage and curing and molding stage. Among them: the fluidity and uniform dispersion of the mixed system are required in the mixing stage; the fluidity and stability of the uniform dispersion of the system are required in the pouring and molding stage; and the uniform dispersion state needs to be maintained until solidification in the molding and curing stage. At present, the biggest problem encountered in the preparation of cement-based materials is that it is difficult to maintain the uniform dispersion of system components in the mixing stage, pouring and molding stage and curing stage. There are phenomena such as water seepage, segregation, sand and gravel sedimentation and stratification, which leads to uneven distribution of structural components of cement-based materials, strength that does not meet the expected target, and easy cracks and leakage.
[0004] The core and key to solving the above problems is to use admixtures with dispersing and suspending effects to regulate the dispersion state of cement paste and sand and gravel, so that the cement paste has appropriate viscosity and fluidity, and can coat the sand and gravel in the cement paste, so that the cement-based material has good fluidity and durable uniform dispersion. However, existing admixtures include cement water reducers and cement paste clay regulators, which generally have poor durable bonding ability and weak dispersion and suspension capabilities for sand and gravel. Therefore, it is difficult to maintain uniform dispersion of cement-based materials during mixing, injection molding and curing stages. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a modified starch cement-based material mixing state regulator, a preparation method and an application. The regulator can give the cement slurry good fluidity and dispersion uniformity, maintain the uniformity of the cement slurry and sand and gravel distribution during the injection molding and curing stages, and significantly improve the structural uniformity and performance of the cement-based material.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a modified starch cement-based material mixing state regulator comprises the following steps:
[0008] Step 1, according to the mass parts, add 40-45 parts of sodium starch octenyl succinate and 3-4 parts of sodium alginate to 120-130 parts of deionized water, heat to 70-80° C. under stirring, continue stirring to form a sodium starch octenyl succinate solution, and keep warm for use;
[0009] Step 2: Add 28 to 32 parts of acrylic acid, 8 to 12 parts of acrylamide, and 6 to 8 parts of hydroxyethyl acrylate to 50 to 60 parts of deionized water in parts by mass to form a monomer mixed solution;
[0010] Step 3: According to the weight percentage, 90 to 110 parts of the monomer mixed solution and 40.5 to 51.0 parts of the initiator solution with a mass fraction of 1.5% to 2.2% are slowly added to 160 to 175 parts of the sodium starch octenyl succinate solution at the same time, and the mixture is stirred and reacted at 70 to 80° C. for 150 to 180 minutes, then cooled to 30 to 40° C., and the pH value is adjusted to 7.0 to 7.5 with an alkaline solution to obtain a modified starch cement-based material mixing state regulator.
[0011] Furthermore, in the structure of the sodium starch octenyl succinate in step 1, there is an average of 1 octyl substituent per 50 glucose units, and its molecular weight is 2000-10000.
[0012] Furthermore, the stirring time in step 1 is 30 to 40 minutes.
[0013] Furthermore, the purity of acrylic acid, acrylamide and hydroxyethyl acrylate in step 2 is greater than 99%.
[0014] Furthermore, the initiator solution in step 3 is prepared by the following method:
[0015] In parts by mass, 0.5 to 0.8 parts of ammonium persulfate and 0.1 to 0.3 parts of thioglycolic acid are added to 40 to 50 parts of deionized water to form an initiator solution.
[0016] Furthermore, the purity of the ammonium persulfate and thioglycolic acid is greater than 99%.
[0017] Furthermore, in step 3, the monomer mixed solution and the initiator solution are simultaneously and slowly added to the sodium starch octenyl succinate solution for 40 to 50 minutes.
[0018] Furthermore, the alkaline solution in step 3 is a sodium hydroxide solution or a potassium hydroxide solution with a mass fraction of 40%.
[0019] A modified starch cement-based material mixing state regulator.
[0020] The invention discloses an application of a modified starch cement-based material mixing state regulator in cement-based materials. The amount of the modified starch cement-based material mixing state regulator added to the cement-based materials is 0.12% to 0.15% of the weight of the cement.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] The control agent prepared by the present invention can make the cement paste form a state similar to a hydrogel and having thixotropy, and has good fluidity during the mixing and injection molding process, improves the coating uniformity of the cement paste on the sand and gravel and the uniformity of the dispersion of the sand and gravel in the cement paste, and makes the filling of sand and gravel in the cement-based material more dense and uniform, without sedimentation, stratification, segregation, and water seepage; in other words, the control agent of the present invention has the performance of maintaining uniform dispersion and suspension of sand and gravel for a long time, and can maintain the uniform dispersion and stability of each component of the cement-based composite material system during the period when the cement-based material is injected into the mold and waits for curing, thereby improving the coating and suspension of the cement paste in the cement-based material for the sand and gravel, thereby improving the structural uniformity of the cement-based material after curing, and significantly improving the stability, mechanical properties and durability of the cement-based material. DETAILED DESCRIPTION
[0023] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0024] The structure of the sodium starch octenyl succinate selected in Examples 1 to 5 has an average of one octyl substituent per 50 glucose units, and a molecular weight of 2,000 to 10,000.
[0025] The acrylic acid, acrylamide, hydroxyethyl acrylate, ammonium persulfate and thioglycolic acid used in Examples 1 to 5 are all of industrial grade, and the purity is greater than 99%.
[0026] In order to verify the performance of the modified starch cement-based material mixing state regulator prepared in Examples 1 to 5, taking the most common cement-based material (i.e., cement-based concrete) as an example, concrete samples for testing were prepared according to the conventional C40 concrete preparation method in the art. The only difference is that the modified starch cement-based material mixing state regulator prepared in Examples 1 to 5 was added during the preparation of the concrete samples.
[0027] Example 1
[0028] Step 1, according to the mass parts, add 40 parts of sodium starch octenyl succinate and 3 parts of sodium alginate to 120 parts of deionized water, heat to 70°C under stirring, continue stirring for 40 minutes to form a sodium starch octenyl succinate solution, and keep warm for use;
[0029] Step 2: Add 28 parts of acrylic acid, 8 parts of acrylamide, and 6 parts of hydroxyethyl acrylate to 50 parts of deionized water by weight to form a monomer mixed solution;
[0030] Step 3, adding 0.5 parts of ammonium persulfate and 0.1 parts of thioglycolic acid to 40 parts of deionized water by weight to form an initiator solution;
[0031] Step 4: According to the mass fraction, 90 parts of the monomer mixed solution and 40.5 parts of the initiator solution were slowly added to 160 parts of the sodium starch octenyl succinate solution at the same time. The addition time was 40 minutes. Then, at 70°C
[0032] The mixture was stirred and reacted for 180 min, then cooled to 30° C., and the pH value was adjusted to 7.0 with a 40% by mass sodium hydroxide solution to obtain a modified starch cement-based material mixing state regulator;
[0033] Step 5, respectively taking cement, sand, gravel, 10% polycarboxylate water-reducing agent by weight, modified starch cement-based material mixing state regulator and water according to a weight ratio of 446:687:1122:8.9:0.669:165, wherein the addition amount of the modified starch cement-based material mixing state regulator is 0.15% of the weight of cement, and preparing a test sample according to a conventional concrete preparation method, first mixing the modified starch cement-based material mixing state regulator with water and 10% polycarboxylate water-reducing agent to obtain a mixing water and admixture mixed solution, and then adding the solution into the mixture of cement, sand and gravel and stirring evenly, the prepared concrete sample has a strength grade of C40.
[0034] Example 2
[0035] Step 1, according to the mass parts, add 41 parts of sodium starch octenyl succinate and 3 parts of sodium alginate to 120 parts of deionized water, heat to 75°C under stirring, continue stirring for 30 minutes to form a sodium starch octenyl succinate solution, and keep warm for use;
[0036] Step 2: Add 29 parts of acrylic acid, 9 parts of acrylamide, and 6 parts of hydroxyethyl acrylate to 50 parts of deionized water in parts by mass to form a monomer mixed solution;
[0037] Step 3, adding 0.6 parts of ammonium persulfate and 0.15 parts of thioglycolic acid to 40 parts of deionized water by weight to form an initiator solution;
[0038] Step 4: According to the weight percentage, 95 parts of the monomer mixed solution and 43 parts of the initiator solution are slowly added to 165 parts of the sodium starch octenyl succinate solution at the same time, and the addition time is 45 minutes. Then, the mixture is stirred and reacted at 80° C. for 150 minutes, and then the temperature is lowered to 40° C., and the pH value is adjusted to 7.1 with a sodium hydroxide solution with a mass fraction of 40%, to obtain a modified starch cement-based material mixing state regulator;
[0039] Step 5, respectively taking cement, sand, gravel, 10% polycarboxylate water-reducing agent by weight, modified starch cement-based material mixing state regulator and water according to a weight ratio of 446:687:1122:8.9:0.5352:165, wherein the addition amount of the modified starch cement-based material mixing state regulator is 0.12% of the weight of cement, and preparing a test sample according to a conventional concrete preparation method, firstly mixing the modified starch cement-based material mixing state regulator with water and 10% polycarboxylate water-reducing agent to obtain a mixed solution of mixing water and admixture, and then adding the mixed solution into the mixture of cement, sand and gravel and stirring evenly, the prepared concrete sample has a strength grade of C40.
[0040] Example 3
[0041] Step 1, according to the mass parts, add 42.5 parts of sodium starch octenyl succinate and 3.5 parts of sodium alginate to 125 parts of deionized water, heat to 75°C under stirring, continue stirring for 35 minutes to form a sodium starch octenyl succinate solution, and keep warm for use;
[0042] Step 2: Add 30 parts of acrylic acid, 10 parts of acrylamide, and 7 parts of hydroxyethyl acrylate to 55 parts of deionized water by weight to form a monomer mixed solution;
[0043] Step 3, adding 0.65 parts of ammonium persulfate and 0.2 parts of thioglycolic acid to 45 parts of deionized water by weight to form an initiator solution;
[0044] Step 4: According to the weight percentage, 100 parts of the monomer mixed solution and 46 parts of the initiator solution are slowly added to 170 parts of the sodium starch octenyl succinate solution at the same time, and the addition time is 50 minutes. Then, the mixture is stirred and reacted at 75° C. for 165 minutes, and then the temperature is lowered to 30° C., and the pH value is adjusted to 7.2 with a potassium hydroxide solution with a mass fraction of 40%, thereby obtaining a modified starch cement-based material mixing state regulator;
[0045] Step 5, respectively taking cement, sand, gravel, 10% polycarboxylate water-reducing agent by weight, modified starch cement-based material mixing state regulator and water according to a weight ratio of 446:687:1122:8.9:0.5798:165, wherein the addition amount of the modified starch cement-based material mixing state regulator is 0.13% of the weight of cement, and preparing a test sample according to a conventional concrete preparation method, firstly mixing the modified starch cement-based material mixing state regulator with water and 10% polycarboxylate water-reducing agent to obtain a mixed solution of mixing water and admixture, and then adding the mixed solution into the mixture of cement, sand and gravel and stirring evenly, the prepared concrete sample has a strength grade of C40.
[0046] Example 4
[0047] Step 1, according to the mass parts, add 44 parts of sodium starch octenyl succinate and 3.5 parts of sodium alginate to 130 parts of deionized water, heat to 80°C under stirring, continue stirring for 30 minutes to form a sodium starch octenyl succinate solution, and keep warm for use;
[0048] Step 2: Add 31 parts of acrylic acid, 11 parts of acrylamide, and 7 parts of hydroxyethyl acrylate to 60 parts of deionized water by weight to form a monomer mixed solution;
[0049] Step 3, adding 0.7 parts of ammonium persulfate and 0.25 parts of thioglycolic acid to 45 parts of deionized water by weight to form an initiator solution;
[0050] Step 4: According to the weight percentage, 105 parts of the monomer mixed solution and 48.5 parts of the initiator solution are slowly added to 175 parts of the sodium starch octenyl succinate solution at the same time, and the addition time is 40 minutes. Then, the mixture is stirred and reacted at 70° C. for 170 minutes, and then the temperature is lowered to 40° C., and the pH value is adjusted to 7.3 with a potassium hydroxide solution with a mass fraction of 40%, thereby obtaining a modified starch cement-based material mixing state regulator;
[0051] Step 5, respectively take cement, sand, gravel, 10% polycarboxylate water-reducing agent by weight, modified starch cement-based material mixing state regulator and water according to the weight ratio of 446:687:1122:8.9:0.6244:165, wherein the addition amount of the modified starch cement-based material mixing state regulator is 0.14% of the weight of cement, and prepare the test sample according to the conventional concrete preparation method, first mix the modified starch cement-based material mixing state regulator with water and 10% polycarboxylate water-reducing agent to obtain a mixed solution of mixing water and admixture, and then add the mixed solution into the mixture of cement, sand and gravel and stir evenly, and the prepared concrete sample has a strength grade of C40.
[0052] Example 5
[0053] Step 1, according to the mass parts, add 45 parts of sodium starch octenyl succinate and 4 parts of sodium alginate to 130 parts of deionized water, heat to 70°C under stirring, continue stirring for 30 minutes to form a sodium starch octenyl succinate solution, and keep warm for use;
[0054] Step 2: Add 32 parts of acrylic acid, 12 parts of acrylamide, and 8 parts of hydroxyethyl acrylate to 60 parts of deionized water in parts by mass to form a monomer mixed solution;
[0055] Step 3, adding 0.8 parts of ammonium persulfate and 0.3 parts of thioglycolic acid to 50 parts of deionized water by weight to form an initiator solution;
[0056] Step 4: According to the weight percentage, 110 parts of the monomer mixed solution and 51 parts of the initiator solution are slowly added to 175 parts of the sodium starch octenyl succinate solution at the same time, and the addition time is 50 minutes. Then, the mixture is stirred and reacted at 80° C. for 160 minutes, and then the temperature is lowered to 40° C., and the pH value is adjusted to 7.5 with a sodium hydroxide solution with a mass fraction of 40%, thereby obtaining a modified starch cement-based material mixing state regulator;
[0057] Step 5, first take cement, sand, crushed stone, 10% polycarboxylate water-reducing agent by weight, modified starch cement-based material mixing state regulator and water according to the weight ratio of 446:687:1122:8.9:0.5352:165, wherein the addition amount of modified starch cement-based material mixing state regulator is 0.12% of the weight of cement, and prepare the test sample according to the conventional concrete preparation method, first mix the modified starch cement-based material mixing state regulator with water and 10% polycarboxylate water-reducing agent to obtain a mixed solution of mixing water and admixture, and then add the mixed solution into the mixture of cement, sand and crushed stone and stir evenly, and the prepared concrete sample has a strength grade of C40.
[0058] Comparative Example
[0059] Without adding the modified starch cement-based material mixing state regulator prepared in Examples 1 to 5, cement, sand, crushed stone, 10% by mass of a polycarboxylate water reducer and water were mixed in a mass ratio of 446:687:1122:8.9:165 according to the preparation method of C40 concrete to prepare a concrete sample.
[0060] The slump, compressive strength, flexural strength, water permeability resistance, freeze-thaw resistance, chloride ion permeability and carbonation resistance of the concrete samples prepared in Examples 1 to 5 and the comparative example were tested respectively, and the volume shrinkage rate of the samples was calculated, wherein: the slump was tested according to the method of GB / T50080-2002 "Ordinary Concrete Mixture Performance Test Standard"; the compressive strength and flexural strength were tested according to the method of GB50107-2010 "Concrete Strength Inspection and Evaluation Standard"; the water permeability was tested according to the GB / T50082-2009 method, the sample size was φ150mm×150mm, the penetration pressure was 3.5MPa, and the pressurization time was 48h; the freeze-thaw resistance was tested according to JTG E30-2005 "Test Procedure for Cement and Cement Concrete for Highway Engineering", using a quick freezing tester to measure the antifreeze performance of concrete, one freeze-thaw cycle lasts 2 to 5 hours, freeze-thaw temperature is -18°C, and the sample size is 100mm×100mm×500mm; chloride ion permeability is measured according to GB / T50082-2009 method for chloride ion diffusion electricity, and chloride ion penetration capacity is evaluated, with a sample size of 100mm×100mm×100mm; carbonization samples are tested according to GB / T50082-2009 method "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", with a sample size of 100mm×100mm×100mm. The performance test results of the concrete samples prepared by Examples 1 to 5 and Comparative Examples are detailed in Table 1;
[0061] Table 1 Performance test results of concrete samples prepared in Examples 1 to 5 and Comparative Examples
[0062]
[0063] As can be seen from Table 1, the concrete samples prepared in Examples 1 to 5 have significantly improved stability, mechanical properties and durability compared to the concrete samples prepared in the comparative example, as shown in: first, they have good slump retention and excellent working performance; second, the compressive strength and flexural strength reach 63.8-66.3MPa and 8.5-9.1MPa respectively, which are much higher than 44.2MPa and 6.4MPa of the comparative sample, indicating that they have good toughness; third, the water seepage height is 0.2-0.3mm, which is less than 0.5mm of the comparative example, indicating that their structure is more compact and has good anti-penetration performance; fourth, the chloride ion penetration level is level 4, It is higher than level 3 of the comparative example, more durable and has a longer service life; fifth, in the 28-day anti-freezing test results, the mass loss is 0, and the maximum loss of dynamic modulus is 0.2%, which is much lower than 10% and 5.6% of the comparative example; sixth, the carbonization resistance depth is 0.1-0.2mm, which is lower than 0.6mm of the comparative example, and has good durability; seventh, the 28-day volume shrinkage rate is 0.1-0.12, which is significantly lower than 0.25% of the comparative example, indicating good volume stability; the above is sufficient to illustrate that the modified starch cement-based material mixing state regulator prepared in Examples 1 to 5 can give cement-based materials good working performance, volume stability and durability.
Claims
1. A method for preparing a modified starch cement-based material mixing state regulator, characterized in that: The steps include: Step 1, according to the mass parts, add 40-45 parts of sodium starch octenyl succinate and 3-4 parts of sodium alginate to 120-130 parts of deionized water, heat to 70-80° C. under stirring, continue stirring to form a sodium starch octenyl succinate solution, and keep warm for use; Step 2: Add 28 to 32 parts of acrylic acid, 8 to 12 parts of acrylamide, and 6 to 8 parts of hydroxyethyl acrylate to 50 to 60 parts of deionized water in parts by mass to form a monomer mixed solution; Step 3: According to the weight percentage, 90 to 110 parts of the monomer mixed solution and 40.5 to 51.0 parts of the initiator solution with a mass fraction of 1.5% to 2.2% are slowly added to 160 to 175 parts of the sodium starch octenyl succinate solution at the same time, and the mixture is stirred and reacted at 70 to 80° C. for 150 to 180 minutes, then cooled to 30 to 40° C., and the pH value is adjusted to 7.0 to 7.5 with an alkaline solution to obtain a modified starch cement-based material mixing state regulator.
2. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: In the structure of the sodium starch octenyl succinate in step 1, there is one octyl substituent per 50 glucose units on average, and the molecular weight is 2000-10000.
3. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: The stirring time in step 1 is 30 to 40 minutes.
4. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: The purity of acrylic acid, acrylamide and hydroxyethyl acrylate in step 2 is greater than 99%.
5. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: The initiator solution in step 3 is prepared by the following method: In parts by mass, 0.5 to 0.8 parts of ammonium persulfate and 0.1 to 0.3 parts of thioglycolic acid are added to 40 to 50 parts of deionized water to form an initiator solution.
6. The method for preparing the modified starch cement-based material mixing state regulator according to claim 5, characterized in that: The purity of the ammonium persulfate and thioglycolic acid is greater than 99%.
7. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: In the step 3, the monomer mixed solution and the initiator solution are slowly added to the sodium starch octenyl succinate solution simultaneously for 40 to 50 minutes.
8. The method for preparing the modified starch cement-based material mixing state regulator according to claim 1, characterized in that: The alkaline solution in step 3 is a sodium hydroxide solution or a potassium hydroxide solution with a mass fraction of 40%.
9. A modified starch cement-based material mixing state regulator prepared by the method according to any one of claims 1 to 8.
10. Use of the modified starch cement-based material mixing state regulator as claimed in claim 9 in cement-based materials, characterized in that: The amount of the modified starch cement-based material mixing state regulator added to the cement-based material is 0.12% to 0.15% of the weight of the cement.
Citation Information
Patent Citations
Cement water-reducing agent and preparation method thereof
CN108439841A
Starch-based polycarboxylate superplasticizer mate as well as preparation method and use method thereof
CN111592619A
Concrete admixture and preparation method thereof
CN114133163A
Collapse-retaining water reducing agent and preparation method thereof
CN115368054A
Double-network polymer in-situ toughened cement-based material and preparation method thereof
CN117125938A